Collaborative learning in a multilingual class - Deonarain Brijlall (Pythagoras, 2008)
The solving of word problems dealing with fractions  was  investigated. Two sets of learners worked in solving the same tasks on fractions. One set of learners worked collaboratively  and the other group consisted of learners working independently.  The selected participants consisted of two Grade 8 classes at a high school in Pietermaritzburg, South Africa.  The study was a qualitative one  involving lesson observations, analysis of learner worksheets, questionnaires and interviews. The two tasks were presented in the form of word problems and the classroom comprised of multilingual learners.  Data yielded by these research instruments confirmed assumptions and literature claims. Although it was a small scale qualitative research, interesting observations were made that could have pedagogical implications.